Strain Hardening From Elastic-Perfectly Plastic to Perfectly Elastic Indentation Single Asperity Contact - Ghaednia, Hamid; Mifflin, Gregory; Lunia, Priyansh; O'Neill, Eoghan O.; Brake, Matthew R. W. (Frontiers in Mechanical Engineering, 2020)
Indentation measurements are a crucial technique for measuring mechanical properties. Although several contact models have been developed to relate force-displacement measurements with the mechanical properties, they all consider simplifying assumptions, such as no strain hardening, which significantly affects the predictions. In this study, the effect of bilinear strain hardening on the contact parameters for indentations is investigated. Simulations show that even 1% strain hardening causes significant changes in the contact parameters and contact profile. Pile-up behavior is observed for elastic-perfectly plastic materials, while for strain hardening values greater than 6%, only sink-in (i.e., no pile-up) is seen. These results are used to derive a new, predictive formulation to account for the bilinear strain hardening from elastic-perfectly plastic to purely elastic materials.